A cooperative multicriteria group decision aiding tool: a guide tour of the desktop application - Fernandes, Sérgio (2018)
Trabalho apresentado na 17th International Conference on Group Decision and Negotiation, 14-18 agosto de 2017, Estugarda, Alemanha